Phraseological Variations in Medical-Pharmaceutical Terminology and its Applications for English and German into Spanish Translations - Francisco Bautista Becerro (Ital Publication, 2020)
One of the main characteristics of medical-pharmaceutical language is its extensive, specific and specialized terminology. In texts of this type, precision and accuracy are key factors, and terminological univocity is sought, even though this is not always feasible. Therefore, it is very common to find phraseological units with term value and even periphrases composed of several words. This phenomenon is common in all fields of expertise and, of course, in colloquial language as well, and it is also relevant in medical-pharmaceutical language and in many cases must be taken into account. The purpose of this publication is to analyse certain situations in which terms from the medical-pharmaceutical field have a different phraseological structure in English or German than in Spanish and some types of cases that we may encounter. We not only study these variations and differences between languages, but also the consequences of a poor translation and the possible strategies to avoid it.